2017
DOI: 10.3390/genes8110315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lateral Transfers on the Genomes of Lepidoptera

Abstract: Transfer of DNA sequences between species regardless of their evolutionary distance is very common in bacteria, but evidence that horizontal gene transfer (HGT) also occurs in multicellular organisms has been accumulating in the past few years. The actual extent of this phenomenon is underestimated due to frequent sequence filtering of “alien” DNA before genome assembly. However, recent studies based on genome sequencing have revealed, and experimentally verified, the presence of foreign DNA sequences in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 135 publications
(207 reference statements)
1
20
0
Order By: Relevance
“…Unraveling the mechanisms and extent of PDV integration events (i.e., investigating integration of other circles and integration in other tissues, including germinal cells) will not only allow us to better understand virulence strategies developed by parasitoid wasps to successfully parasitize their lepidopteran hosts but might also provide the mechanism of recently uncovered horizontal gene transfer between parasitic wasps, PDVs, and the genomes of moths and butterflies. Indeed, in some cases CcBV DNA containing genes of wasp origin have been found to be present in the genomes of many lepidopteran species, including the iconic Monarch species (61)(62)(63). However, unlike BV sequences identified in C. sesamiae wasps, we could not find a complete circle inserted in the genome of Lepidoptera, which could be due to the fact that the insertions are ancient and have undertaken many rearrangements after circle integration.…”
Section: Discussionmentioning
confidence: 58%
“…Unraveling the mechanisms and extent of PDV integration events (i.e., investigating integration of other circles and integration in other tissues, including germinal cells) will not only allow us to better understand virulence strategies developed by parasitoid wasps to successfully parasitize their lepidopteran hosts but might also provide the mechanism of recently uncovered horizontal gene transfer between parasitic wasps, PDVs, and the genomes of moths and butterflies. Indeed, in some cases CcBV DNA containing genes of wasp origin have been found to be present in the genomes of many lepidopteran species, including the iconic Monarch species (61)(62)(63). However, unlike BV sequences identified in C. sesamiae wasps, we could not find a complete circle inserted in the genome of Lepidoptera, which could be due to the fact that the insertions are ancient and have undertaken many rearrangements after circle integration.…”
Section: Discussionmentioning
confidence: 58%
“…Following a number of reports of TE insertions in baculoviruses [3842], recent surveys based on deep sequencing of viral genomes have revealed an abundant presence of host TEs, some of which match documented cases of HTT [11,12]. Based on these findings, the high potential of baculoviruses as vectors of HTT in Lepidoptera has been previously emphasized [3]. Some authors have even explicitly suggested that considering the high prevalence of baculoviruses in Lepidoptera, an elevated HTT rate in that clade would provide support for their implication [20] (page 271).…”
Section: Discussionmentioning
confidence: 99%
“…Some HGTs have provided new functionality and enabled the recipients to acquire traits that facilitate nutrition, protect against adverse environments, contend with toxic diets, and, for our purposes here, adapt to host plants in the case of herbivores (Husnik & McCutcheon, ). The co‐opting of microbial genes from bacteria, baculoviruses, polydnaviruses (PDVs; especially bracoviruses), and fungi has shaped the genomes of many herbivorous insects: Lepidoptera (Drezen, Josse, et al, ), Coleoptera (Kirsch et al, ), and others (Wybouw, Van Leeuwen, & Dermauw, ). Such HGT events have enabled herbivore speciation and the successful colonization of host plants.…”
Section: Hgt: Host Facilitation and Potential Role In Plant Signallingmentioning
confidence: 99%